Use of Organic Enrichment as Additives in Coconut Coir Dust Soilles Culture for Growth and Yield of Tomatoes (Lycopersicon Esculentum Mill. cv. Beril) - Mokhtari, Solmaz (2010)
Soilless culture is an artificial means of providing support for plants as well as a reservoir for nutrients and water, and is becoming an important part of world agriculture. In Malaysia there is a rapid expansion on the use of locally produced coconut coir dust (CD) as a growth media. The main limitation in using this media its low cation exchange capacity (CEC) and poor water retention that can affect plant development. These limitations may be overcome with organic amendments. Hence, the main objective of this study was to determine the effect of different concentrations of empty fruit bunch (EFB) and vermicompost (VC) as additives on the growth and yield of tomato plants grown in coconut coir dust media. Experiments were conducted on 100% CD (control) with nutrient solution (EC=2.5 mScm-1), and 30% of EFB with 70% CD, 10% VC with 90% CD, 20% VC with 80% CD, 30% VC with 70% CD and 40% VC with 60% CD (on pot volume basis)in which the nutrient concentrations was half of those supplied in the control. The results showed that plants grown in CD with 20% and 10% of VC had higher growth and yield compared to plants grown in 100% CD or CD mixed with EFB. Total yield and fruit quality of tomatoes were improved by vermicompost amendment as additive in the coconut coir based media. The investigation on tissue nutrient content showed high accumulation of N, P, K, Ca and Mg in organic enrichment (EFB and VC) media in comparison to the control (100% CD). The N uptake in shoots from enrichment with half of nutrient concentration (EC=1.25 mScm-1) was more (EFB = 46.52 mg/plot and 20%VC= 30.96 mg/plot) than in shoots from the control with EC =2.5 mScm-1 (29.48 mg/plot). Results on tomato fruit analysis showed higher heavy metal concentrations in CD with high electrical conductivity of 2.5 mS cm-1. Fruits obtained in the three amended media had Zn, Cu and Cd concentrations below UK Guidelines (1989). Pb concentration was also within safe limits according to international guidelines (UK Guidelines, 1989). Overall, these results suggest that with the use of organic amendments lower volume of chemical nutrients can be used to achieve good yield in soilless culture.